(untitled) (Journal of Computational Mathematics, 2001)
In this contribution we analyse some fundamental features of an iterative method to solve systems of linear equations, following the approach introduced in a previous work [1]. Such questions range from optimal parameters and initial conditions to comparison with other methods. An interesting result is that a priori we can give an estimation of the number of iterations to get a given accuracy.